Safety of fibrinogen concentrate: analysis of more than 27 years of pharmacovigilance data - Solomon, Cristina; Gröner, Albrecht; Jian, Ye; Inna, Pendrak (Thrombosis and Haemostasis, 2015)
Fibrinogen concentrate use as a haemostatic agent has been increasingly explored. This study evaluates spontaneous reports of potential adverse drug reactions (ADRs) that occurred during postmarketing pharmacovigilance of Haemocomplettan P/RiaSTAP, and reviews published safety data. This descriptive study analysed postmarketing safety reports recorded in the CSL Behring pharmacovigilance database from January 1986 to December 2013. A literature review of clinical studies published during the same period was performed. Commercial data indicated that 2,611,294 g of fibrinogen concentrate were distributed over the pharmacovigilance period, main-contribonding to 652,824 standard doses of 4 g each, across a range of clinical settings and indications. A total of 383 ADRs in 106 cases were reported (approximately 1 per 24,600 g or 6,200 standard doses). Events of special interest included possible hypersensitivity reactions in 20 cases (1 per 130,600 g or 32,600 doses), possible thromboembolic events in 28 cases (1 per 93,300 g or 23,300 doses), and suspected virus transmission in 21 cases (1 per 124,300 g or 31,000 doses). One virus transmission case could not be analysed due to insufficient data; for all other cases, a causal relationship was assessed as unlikely due to negative polymerase chain reaction tests and/or alternative explanations. The published literature revealed a similar safety profile. In conclusion, underreporting of ADRs is a known limitation of pharmacovigilance. However, the present assessment indicates that fibrinogen concentrate is administered across a range of indications, with few ADRs and a low thromboembolic event rate. Overall, fibrinogen concentrate showed a promising safety profile.Institution to which work should be attributed: CSL Behring, Marburg, Germany.
Keywords: Fibrinogen; pharmacovigilance; safety